2015
DOI: 10.1371/journal.pone.0125828
|View full text |Cite
|
Sign up to set email alerts
|

Viroporin Activity of the Foot-and-Mouth Disease Virus Non-Structural 2B Protein

Abstract: Viroporins are a family of low-molecular-weight hydrophobic transmembrane proteins that are encoded by various animal viruses. Viroporins form transmembrane pores in host cells via oligomerization, thereby destroying cellular homeostasis and inducing cytopathy for virus replication and virion release. Among the Picornaviridae family of viruses, the 2B protein encoded by enteroviruses is well understood, whereas the viroporin activity of the 2B protein encoded by the foot-and-mouth disease virus (FMDV) has not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
70
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 65 publications
3
70
0
Order By: Relevance
“…7C). Following the pattern previously described to occur in Vero and BHK-21 cells (7,14), the wild-type fusion protein GFP (green fluorescent protein)-2B colocalized with the ER marker mCh-Sec61 beta in 293T cells. Mutants 2B.1, 2B.3, 2B.11, and 2B.13 displayed significantly lower Pearson colocalization indexes, indicating that alteration of the transmembrane structures interfered with the biogenesis of the 2B protein in these instances.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…7C). Following the pattern previously described to occur in Vero and BHK-21 cells (7,14), the wild-type fusion protein GFP (green fluorescent protein)-2B colocalized with the ER marker mCh-Sec61 beta in 293T cells. Mutants 2B.1, 2B.3, 2B.11, and 2B.13 displayed significantly lower Pearson colocalization indexes, indicating that alteration of the transmembrane structures interfered with the biogenesis of the 2B protein in these instances.…”
Section: Resultssupporting
confidence: 57%
“…FMDV 2B protein possesses ion channel activity. The FMDV 2B protein has been shown to behave as a viroporin regarding its cytotoxic effects upon overexpression in bacteria and its capacity for altering trafficking along early secretory pathways in animal cells, where it also seems to induce intracellular calcium release and autophagy (7). However, membrane permeability measurements investigating its pore formation mechanisms at the molecular level had not yet been performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study demonstrated that 2B is a membrane-associated protein that acts as a viroporin and that 2B can induce intense autophagy in BHK-21 cells, thereby enhancing the release of viruses (48). The multiple alignment of the 2B coding sequences showed that it is highly conserved among all seven serotypes of FMDV (48).…”
Section: Discussionmentioning
confidence: 99%
“…The multiple alignment of the 2B coding sequences showed that it is highly conserved among all seven serotypes of FMDV (48). This implies that 2B contributes to the increased virus propagation and is associated with the infection mechanism of FMDV.…”
Section: Discussionmentioning
confidence: 99%